2021
DOI: 10.1186/s11671-021-03545-8
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Activated Carbon from a Bio-Waste Desmostachya bipinnata for the Improved Supercapacitor Performance

Abstract: Herein, we demonstrate the fabrication of highly capacitive activated carbon (AC) using a bio-waste Kusha grass (Desmostachya bipinnata), by employing a chemical process followed by activation through KOH. The as-synthesized few-layered activated carbon has been confirmed through X-ray powder diffraction, transmission electron microscopy, and Raman spectroscopy techniques. The chemical environment of the as-prepared sample has been accessed through FTIR and UV–visible spectroscopy. The surface area and porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…In our case, ID/IG ratio is observed to be 0.93 and corresponds to the activated carbon [33] . Moreover, the presence of a 2D band at ∼2700 cm −1 (two phonons double resonance phenomenon) reveals the presence of a few layers of graphene oxide nanosheets [34] …”
Section: Resultsmentioning
confidence: 99%
“…In our case, ID/IG ratio is observed to be 0.93 and corresponds to the activated carbon [33] . Moreover, the presence of a 2D band at ∼2700 cm −1 (two phonons double resonance phenomenon) reveals the presence of a few layers of graphene oxide nanosheets [34] …”
Section: Resultsmentioning
confidence: 99%
“…According to the available literature, the π–π* transition occurs in the range of 180–260 nm for carbon material . Gupta et al reported a characteristic UV–vis absorption peak at 264 nm for AC derived from Kusha grass . Thus, an excitation wavelength of 264 nm was utilized for the PL study and is presented in Figure S5 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…73 Gupta et al reported a characteristic UV−vis absorption peak at 264 nm for AC derived from Kusha grass. 74 Thus, an excitation wavelength of 264 nm was utilized for the PL study and is presented in Figure S5 in the Supporting Information. The PL spectra reveal identical curve shapes for BFF and ABFF carbon with two distinct emission bands at ∼416 and 440 nm.…”
Section: °+ →mentioning
confidence: 99%
“…Additional studies are essential to minimize the main knowledge gaps in the field of sustainable materials for energy storage applications. This review shows that relatively inexpensive and renewable resources from plants are (Gupta et al, 2021) Thilageshwaran Subramaniam , Mohamed Ansari Mohamed Nainar and Noor Afeefah Nordin highly porous carbon and can be converted into useful products, such as supercapacitors for energy storage applications, which are expected to be in great demand in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AC-SPN-3 has the highest specific capacitance of 313 and 215 F/g in 6M KOH and TMABF 4 electrolytes, respectively, compared to other samples as shown in Figure 14(b). Gupta et al (2021) synthesized activated carbon from Desmostachya bipinnata (Kusha grass) and studied its electrochemical performance as a supercapacitor electrode (Gupta et al, 2021). The description of steps involved in the DP-AC synthesis is as shown in Figure 15.…”
Section: Characterization Of Activated Carbon-based Supercapacitor Electrodementioning
confidence: 99%